Variáveis clínicas preditoras de sucesso do tratamento por Escleroterapia com espuma de Polidocanol 1% em malformações vasculares de baixo fluxo: estudo coorte prospectivo - Betânia Almeida Nadalin Leal (2024)
Introduction: Vascular malformations are anomalous groupings of blood or lymphatic vessels that are formed during embryogenesis. They can affect any part of the body and cause different symptoms. The treatment remains controversial, and sclerotherapy has been the first choice in low flow vascular malformation. Purpose: To assess the efficacy and safety of sclerotherapy with 1% polidocanol foam in the short and medium term in low-flow vascular malformations and to analyze the correlation of symptom improvement with clinical variables. Methods: Prospective cohort study of symptomatic low flow vascular malformation in patients treated in Hospital das Clínicas da UFMG, between December 2016 and July 2023. Lesions were classified according to the location, extension, size, type of vessels, shape, and symptoms. Treatment was done through 1% polidocanol foam injection, and the maximum volume of foam was 10 ml per session with a liquid-to-air ratio of 1:4. It was made an assessment to the improvement of the symptoms with analogic visual scale and patient-reported quality of life was assessed by the Short-form 6 dimensions (SF-6D) questionnaire. It was recorded the existence of complications, and the lesions were photographed before and after. Follow up was done each 3 months after the treatment. Results: Seventynine lesions in 73 patients were enrolled, being 31 males. Age ranged from 4 months to 66 years. The minimum time of follow up was of 3 months and the maximum was 79 months, with a media of 36 months. Most lesions (88,6%) were venous. The most common locations were lower limbs (44,3%), followed by upper limbs (24%) and head (21,5%). Regarding the extension, 29,1% were superficial, 27,8% were deep lesions and 43% affected both compartments. The most common clinical presentation was deformity (86%), followed by pain (77,2%) and functional limitation (59,4%). There was a significant improvement of all symptoms (p<0,001). The functional limitations were more often in lesions affecting the deep compartment compared to the superficial ones (p=0,047). A diameter of less than 10 cm and superficial involvement were associated with a good/complete response to the deformity (p<0.001). On the other hand, the improvement of functional limitation was associated with the superficial compartment (p=0.049) and the location in the head (p=0.012). There was an improvement in quality of life in most patients (60%) and treatment satisfaction was high (84,7%). The most common complications were pain and local edema, without major complications. There was recurrence of the symptoms in 46% of the patients and 36,7% needed another treatment. Conclusion: Low flow vascular malformations treatment using 1% polidocanol foam is effective and safe. It improves symptoms and quality of life, achieving high patient´s satisfaction scores. Lesion diameter of less than 10 cm and superficial involvement were the predictors of success in the resolution of the deformity, whereas superficial involvement and lesions localized in the head were the predictors of success in functional improvement. A high percentage of patients, however, reported recurrent symptoms and some patients require other modalities for successful treatment.